Stimulating innovative thinking - White, Daniel
Daniel White reports how cognitive coaching can spur technical creativity.
Cognitive coaching, when used alongside proven management techniques, can increase creativity and effectiveness in technical organizations.
Recent research shows that certain types of dialogue can spur technical creativity. Coaching dialogues that support a scientist's autonomy while providing guidance are particularly effective for stimulating innovative thinking. Dialogues in which managers use language that demonstrates respect for the scientist's thinking while attempting to expand it, enhance a scientist's critical sense of autonomy. Dialogues in which managers balance their use of questioning and advising ensure needed mutuality. Managers begin the dialogue approach by understanding the thinking processes associated with innovation. They use this understanding to selectively reinforce and guide those thoughts that can become precursors of innovation. They guide gingerly with questioning and advising skills as they become coaches of innovation.
Keywords: Innovative thinking